The time between trajectories and transformations (Revista de Investigaciones Universidad del Quindío, 2010)
The nature of science and contemporary thought flows on the basis of the “constructive role of time" in irreversible processes, the same that supports what has been the evolution of life and biodiversity on the planet. In that sense, this concept of time occurs as a "revolutionary change" for our culture, meanwhile we can perceive a world where the human things are not foreign to nature as happened with the explanatory domain of classical science. Hence, even considering the undeniable utility and amenities that the development of modern science has given us, actually is not sustainable a simplistic thinking given the highly complex nature of the problems that overwhelm us. In fact, the living conditions of society and the environment of our time at all levels, demand transitions in the ways we inhabit the world, because in this it is played the viability of the human species in the evolution of life. It is surprising how it has changed the conception of science in such a short time to the point that it is possible to affirm a new scientific thinking about the diversity and instability, the dawning of an explanatory domain looks jovial and fruitful
Keywords: Time; causality; determinism; chronology; trajectory; becoming; transformation; thermodynamics; dissipative structures; bifurcation; difference